Immunology of pregnancy - Torres, Carmen (2015)
Pregnancy is an immunological condition in which the fetus acts as a graft semiallogenic expressed antigens inherited from the father, which to be recognized as "non-self by the mother" should generate an immune rejection response. But normally this fact is not given, and the mother does not reject the fetus.